2017
DOI: 10.1073/pnas.1705435114
|View full text |Cite
|
Sign up to set email alerts
|

Direct single-molecule measurements of phycocyanobilin photophysics in monomeric C-phycocyanin

Abstract: Phycobilisomes are highly organized pigment-protein antenna complexes found in the photosynthetic apparatus of cyanobacteria and rhodophyta that harvest solar energy and transport it to the reaction center. A detailed bottom-up model of pigment organization and energy transfer in phycobilisomes is essential to understanding photosynthesis in these organisms and informing rational design of artificial light-harvesting systems. In particular, heterogeneous photophysical behaviors of these proteins, which cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 51 publications
1
35
1
Order By: Relevance
“…Simultaneously, fluorescence brightness (Br), polarization (FPol), lifetime ( τ ), and emission spectrum (Em( λ ), also described by the spectral center of mass, λ CM ) are monitored for each trapped particle. The ABEL trap is well suited to characterize individual phycobiliproteins 6264 and other photosynthetic protein complexes 6567 because it does not require analyte immobilization, which might perturb the spectroscopic properties or energy transfer in these delicate structures (see Supplementary Note 2 for additional discussion).
Fig. 2Anti-Brownian trapping of single unquenched and quenched phycobilisomes.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, fluorescence brightness (Br), polarization (FPol), lifetime ( τ ), and emission spectrum (Em( λ ), also described by the spectral center of mass, λ CM ) are monitored for each trapped particle. The ABEL trap is well suited to characterize individual phycobiliproteins 6264 and other photosynthetic protein complexes 6567 because it does not require analyte immobilization, which might perturb the spectroscopic properties or energy transfer in these delicate structures (see Supplementary Note 2 for additional discussion).
Fig. 2Anti-Brownian trapping of single unquenched and quenched phycobilisomes.
…”
Section: Resultsmentioning
confidence: 99%
“…The ABEL trap 63 , 64 was implemented using a linearly polarized, 80 MHz pulsed-excitation laser (Coherent Mira OPO), loosely focused to a 0.6-µm beam waist in the sample plane. The beam was scanned in a knight’s tour pattern in the trapping region of a microfluidic cell over a 32-point 2 × 2 µm grid with pitch 0.4 µm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 These steps must be implemented quickly enough to overcome the diffusive motion of the particle, and significant recent progress has been made toward optimizing this control loop to enable trapping of individual small organic fluorophores. 28,34 Trap implementations that utilize either intrinsic or label-based fluorescence to track emissive particles have been employed to characterize time-varying photophysical states, [35][36][37][38][39][40] molecular dynamics and kinetics, [41][42][43][44][45][46][47] and more. [48][49][50] However, the trapping duration, and therefore data collection, in anti-Brownian traps is typically limited by photobleaching or by blinking because dark particles cannot be tracked and are quickly lost.…”
mentioning
confidence: 99%
“…Moreover, they can also be used as natural dyes in the food industry and pharmaceuticals products [ 86 ]. From direct single-molecule measurements of C-PC in EET, by monitoring the fluorescence emission from single photosynthetic antenna proteins in a free solution over a long time and within the FRET theoretical framework, it has been found that there are transitions among many different photophysical states exhibiting distinct EET pathways among the embedded pigments [ 87 ]. These numerical findings would not be accessible by bulk studies underscoring the importance of a molecular approach.…”
Section: Introductionmentioning
confidence: 99%